Dynamic shear rheometer testing and mechanistic conversion to predict bending beam rheometer low temperature behavior of bituminous binder. (18th January 2021) - Kommidi, Santosh Reddy; Kim, Yong-Rak
Highlights: DSR test results were converted to BBR beam deflection. The conversion was conducted by elastic-viscoelastic correspondence principle. An analytical model with a calibration factor was proposed. DSR method at low temperatures can predict the BBR beam deflection. DSR can be a potential supplemental method to the BBR with testing efficiency. Abstract: The low-temperature rheology of bituminous binders is of great interest because low-temperature cracking is one of the primary failure modes of asphaltic pavements in cold-climate region. Low temperature binder characterization/grading has been primarily conducted using the bending beam rheometer (BBR) which requires much binder for specimen preparation, labor-intensive and time-consuming to conduct the testing. In contrast, the dynamic shear rheometer (DSR) testing is much easier, faster, and has brought a lot attention to the community because it requires less than one gram per specimen and is applicable for both laboratory-prepared and field-extracted binder for forensic analysis. This study explored using the DSR to characterize low temperature behavior of binder. To this end, both DSR and BBR tests were conducted, and the DSR test results were mechanically converted to BBR beam deflection using the elastic-viscoelastic correspondence principle. Two groups of binders (i.e., twelve binders from four different sources satisfying three different low temperature grades as one group to investigate the feasibility of the concept, and seven additional binders to apply the concept to a separate group of binders as the second group) were selected and tested under the long term aged condition. More specifically, the dynamic frequency sweep test data from DSR were used to obtain the time-dependent creep compliance that is used in the analytical equation for predicting the BBR beam deflection over time. Test-analysis results demonstrate that the DSR low temperature testing and its mechanistic conversion is promising as it can predict the BBR beam deflection, while a calibration factor can improve the predicting power of creep stiffness, and an additional horizontal shifting was helpful to give a better agreement of the slope ( m -value). Although actual implementation into practice requires a more careful investigation, this study infers that the DSR testing can be a good supplemental (or alternative) method to the BBR, which can benefit experimental efficiency of many state highway agencies.